Counselling services management and social application - Lok, Xuan Wen (2022)

(untitled)
This project is a development-based project with the aim of developing a counselling services management website with an integration of social platform for the Guidance and Counselling Unit of UTAR Kampar. This project mainly caters UTAR counsellors and students where all counselling services will be conducted within the same platform. It is developed to facilitate online counselling and documentation process of the counselling unit as UTAR’s current counselling system strongly relies on hard copy documentation and diverse platforms to conduct some of the modules or main features include appointment scheduling system, past records and online peer support community for mental health which encourages the registered students to engage and socialize with each other along the recovery journey. Prior to the development of this project, thorough research and a detailed review were conducted to analyse existing online counselling and mental health support applications on the market to determine the benefits and limitations. This project is initialized with the aid of flow charts, use case diagrams and activity diagrams to visualize the project overview. The methodology chosen for this project would be Extreme Programming (XP) and the application will be developed in HTML, CSS, JavaScript, and PHP with Visual Studio Code as the integrated development environment (IDE). XAMPP will be used as the local host server for this project where MySQL will act as the database server whereas Gmail SMTP will be integrated to setup the SMTP server for email verification purposes.